2020
DOI: 10.1002/admi.201901777
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Stability of Hybrid Perovskite Thin‐Film Transistors by Ambient Air Processing

Abstract: Despite the widespread research on organic–inorganic hybrid perovskites, the ambient air instability and ion migration‐induced hysteresis in the current–voltage characteristics of their devices remain unsolved. Here, it is shown that stable ambient air operation of methylammonium lead iodide (MAPbI3) thin‐film transistors can be achieved by solution processing of the MAPbI3 film in ambient air via solvent engineering. N,N‐dimethylformamide (DMF), mixed with dimethyl sulfoxide (DMSO) and hydroiodic acid (HI), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Previous studies have shown the presence of oxygen during annealing to reduce defects without affecting the surface morphology [ 37 , 38 ]. Moreover, it is suggested that oxygen reduces grain boundary defects, yielding better grain-to-grain connection, which is essential for good lateral conduction [ 24 ]. The presence of oxygen in the films ( Figure 4 ) was consistent with defect passivation during ambient air processing [ 21 , 24 , 25 , 38 , 39 ] and evaporation of MA via oxygen bonding at temperatures greater than 120 °C ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown the presence of oxygen during annealing to reduce defects without affecting the surface morphology [ 37 , 38 ]. Moreover, it is suggested that oxygen reduces grain boundary defects, yielding better grain-to-grain connection, which is essential for good lateral conduction [ 24 ]. The presence of oxygen in the films ( Figure 4 ) was consistent with defect passivation during ambient air processing [ 21 , 24 , 25 , 38 , 39 ] and evaporation of MA via oxygen bonding at temperatures greater than 120 °C ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, we found temperatures around 70 °C to be sufficient for the seed formation. Given the high boiling points of GBL and DMSO (204 and 189 °C, respectively) [ 24 ], high-temperature annealing is required after SCG to effectively complete crystallization. This temperature should be around 120 °C, according to Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations